PENGEMBANGAN KOMPETENSI SUMBERDAYA MANUSIA TERHADAP PENINGKATAN KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KONAWE - Yunila Yunila SE, M.Si; Sri Widati; Milyan Milyan (Cakrawala Management Business Journal, 2021)
Abstract The study in this study is the development of human resource competencies in the Department of Population and Civil Registration, with the aim of knowing and analyzing and using a qualitative descriptive approach. Data was collected by using interview, observation and document review techniques. Data analysis used primary and secondary data which were collected and analyzed descriptively. The results of this study indicate that the competence of human resources in the Department of Population and Civil Registration, technical competence has not been maximally implemented by employees, while managerial competence and social competence have run as expected. This can be seen from the dominant number of ASN personnel who have undergraduate education and have fairly good abilities or competencies, but still need to be improved so that employee performance also increases, then in providing services they do not discriminate between ethnicity, religion and culture. The performance of employees at the Office of Population and Civil Registration of Konawe Regency revealed that the assessment of the ability of employees, namely the education factor, was quite good. Keywords: Competence, human resources, performance